Elucidating Sensing Mechanisms of a Pyrene Excimer-Based Calix[4]Arene for Ratiometric Detection of Hg(Ii) and Ag(I) and Chemosensor Behaviour as Inhibition or Implication Logic Gates - Godoy-Gonzalez, F; Godoy-Gonzalez, F; Flores-Vergara, E; Flores-Vergara, E (Royal Society of Chemistry, 2020)
This article reports the synthesis and characterisation of two lower rim calix[4]arene derivatives with thiourea as spacer and pyrene or methylene-pyrene as fluorophore. Both derivatives exhibit a fluorimetric response towards Hg2+, Ag+and Cu2+. Only methylene-pyrenyl derivative2allows for selective detection of Hg2+and Ag+by enhancement or decrease of excimer emission, respectively. The limits of detection of2are 8.11 nM (Hg2+) and 2.09 nM (Ag+). DFT and TD-DFT computational studies were carried out and used to identify possible binding modes that explain the observed response during fluorescence titrations. Calculations revealed the presence of different binding sites depending on the conformation of2, which suggest a reasonable explanation for non-linear changes in fluorescence depending on the physical nature of the interaction between metal centre and conformer. INHIBITION and IMPLICATION logic gates have also been generated monitoring signal outputs at pyrene monomer (395 nm) and excimer (472 nm) emission, respectively. Thus2is a potential primary sensor towards Ag+and Hg2+able to configure two different logic gate operations. © The Royal Society of Chemistry 2020.